Іnformation and technological competence as a component of the teacher professional competence - Andreev, N.; Markova, V.; Mefanik, M. (Problems of Engineer-Pedagogical Education, 2021)
This article considered the component of professional competence - information and technological competence, which provides effective work of the teacher in the new information society. The concept of "competence" and "competence", "professional teacher competence", "information competence" and "information and technological competence" are analyzed. The essence of informational and technological competence, which is a new direction, which arose directly under the influence of new information technologies and creation of electronic information technologies, was determined. It is noted that the importance of its formation is exacerbated by the rapid development of information and communication technologies, the transformation of our society into information, that is, in a society in which most workers are busy receiving, processing, storing and delivering information. An instructor of any subject discipline should provide students with an example of applying information technology, engaging them with effective methods and means of working with information, thus preparing for life and activities in the information society. The emphasis is placed on the fact that the information and technology competence represents the teacher's ability to effectively apply information and communication technologies not only for the preparation of methodical and didactic material for his subject, but to know and use their capabilities in designing a class, which is impossible without knowledge of the features of the didactic cycle and its implementation in the educational process. Therefore, information and technology competence is an integral part of the professional teacher competence.